Actual Issues of the States Compliance with the Human Rights International Standards - D. V. Ivanov; A. V. Kolesnikova (Московский журнал международного права, 2012)
The article highlights the facts and the reasons influencing the current situation in the field of protection of human rights. The problems of bridging the gap between the “old model of democracy and the new realities” such as the right to vote and the right to education, the gender equality and the women’s empowerment; the situation of children are considered in the article. Also the most important ways of solving the “gender” problems: the rational use of management capabilities and personal qualities of women, the assets, the ability to act and the opportunities that women have; and the expansion of individual and collective abilities of women to act are suggested. Special attention is paid to the contemporary forms of racism, the racial discrimination, the xenophobia and related intolerance, the migration policy.